Simbolisme Tradisi Nyadran Desa Sonoageng sebagai Media Pengayaan Materi Pembelajaran Sastra Siswa SMA di Kabupaten Nganjuk (MARDIBASA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2022)
Literature learning is an important part of learning that must be taught to students. Literature can provide benefits and form a good personality in students. This writing aims to find out the benefits of enriching literary learning materials through local culture which in this case is the traditional symbolism of nyadran. From this writing, the concept of symbolism of the nyadran tradition is found, namely for individuals which include the values of 1) willing to sacrifice, 2) responsibility, 3) obedience, and social meaning which includes the values of 1) mutual cooperation, 2) mutual respect. From this it is expected that students are able to have this attitude and have a superior personality. Thus, it can be concluded that the enrichment of literary learning materials through local culture needs to be done.